Simultaneous optimization of power factor and thermal conductivity via charge transfer effect and enhanced scattering of phonons in Si80Ge20P1/CoSi2 composites - Runze Shi; Jie Gao; Lei Miao; Chengyan Liu; Ying Peng; Jun-Liang Chen; Huajun Lai; Kun Hu (Journal of Materiomics)
SiGe based alloy is a promising medium-high temperature thermoelectric material that has been applied in the field of aerospace exploration. So far, utilizing the second phase to promote the scattering of phonons is a common way to improve the thermoelectric performance of SiGe based alloy, but this often deteriorates the electrical properties. In this study, the Si80Ge20P1/CoSi2 composites have been prepared by mechanical alloying and spark plasma sintering, and the content of cobalt silicide (CoSi2) nanoparticles have been manipulated. Since the CoSi2 nanoparticles possess higher carrier concentration and smaller work function than the Si80Ge20P1 matrix, the carrier concentrations of composites have been pushed up due the charge transfer effect. Meanwhile, the formation of nano-sized phase interfaces and stacking faults in the composites has enhanced the scattering of low-frequency phonons. As a result, the optimal power factor of 3.41 mW⋅m−1⋅K−2 and thermal conductivity of 2.29 W⋅m−1⋅K−1 have been achieved, and the corresponding zT reaches up to 1.3 in the Si80Ge20P1+0.5% CoSi2 (in mole) composite at 873 K. This work provides a new idea for developing the performance of SiGe based alloy.